Frederick Gardner Cottrell papers - Cottrell, Frederick Gardner, 1877-1948.
Correspondence, diaries, writings, scientific papers, notebooks, notes, and other papers relating primarily to Cottrell's career as a research chemist and scientist. Documents his invention of the electrostatic precipitator, his work while a chemist at the U.S. Dept. of Agriculture, and the founding of Research Corporation. Also includes patent papers for Cottrell's process of producing nitric oxide and material concerning inventions of his associates, Farrington Daniels and P.H. Royster. Includes correspondence with Cottrell's associates and Frank Thomas Cameron, author of Cottrell: Samaritan of Science (1952).
Chemist and inventor.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Cameron, Frank Thomas, -- 1909-1984.; Daniels, Farrington, -- 1889-1972.; Royster, P. H. -- 1888-1966.; United States. -- Department of Agriculture; Research Corporation; Chemistry; Electrostatic precipitation; Electrostatic precipitation -- Patents; Nitric oxide; Patents; Science -- History -- 20th century; Chemists; Inventors